The impact of water and sediment quality on the health of clarias gariepinus (burchell, 1822) and labeo rosae (steindachner, 1894) at the Phalaborwa Barrage, Olifants River, Limpopo Province - Mahlatji, Matlale Letticia (University of Limpopo (Turfloop Campus), 2014)
Contamination of aquatic ecosystems by agricultural and mining activities, as well as by industrial discharges and urbanization in the catchment of the South African river systems has been the cause of increasing public concern. These activities may result in water pollution. One such river is the Olifants River System in Mpumalanga and Limpopo provinces which is highly impacted. The main aim of the study was to assess the impact of the water and sediment quality on the health of Clarias gariepinus and Labeo rosae and human risk when the fish is consumed at the Phalaborwa Barrage in the Lower Olifants River, Limpopo Province. This was achieved by assessing the water and sediment quality of the barrage at the three sampling sites; assessing the condition of the fish and the fish parasites by applying the fish HAI (Health Assessment Index) and PI (Parasite Index); determining the bioaccumulation of selected metals in the muscle tissue of the two fish species; and to determine the Human health risk factor upon consumption of fish contaminated with metals at the barrage. Ten fish from each fish species were collected seasonally at each site using gill nets of different mesh sizes. Standards methods were followed when testing selected water and sediment constituents. For water quality sampling, the water samples were collected over four seasons (autumn, winter, spring and summer) at three sites (inflow, wall and below wall) from April 2010 to January 2011. Sediment samples were also collected using a Friedlinger mudgrab (225cm3) at the three sites during winter and summer. Fish hosts were examined for mobile ectoparasites, weighed and measured. Blood samples were drawn and skin smears were made. Fish were killed, dissected and all external and internal organs were examined as prescribed in the fish health assessment index. The condition factor was determined for each fish population. All parasites were collected, fixed and preserved using standard methods. The highest water temperature (28.5 ºC) was in spring and lowest in winter (18 ºC). Overall pH was in an alkaline condition as it ranged from 7.4 to 8.7. Most water quality parameters were recorded at higher concentration in spring which includes; water temperature, pH, conductivity, salinity, TDS, alkalinity, and turbidity. Major ions (cations and anions) recorded were all within the TWQR. Sulphates concentrations were all within the TWQR. Calcium concentration levels exceeded the typical concentration limit in spring but the levels were still within the TWQR for domestic use. Nutrients levels (nitrate, nitrite, sulphate) were very low which indicate oligotrophic conditions. Highest total nitrogen was recorded in spring which is an indicative of eutrophic conditions. Highest phosphorous concentrations were recorded in winter, spring and summer which are an indicative of eutrophic conditions. Noticeable elevated levels were recorded at the inflow in summer which is an indicative of hypertrophic conditions. The results of the metals concentrations analysed demonstrated that metals within the barrage are present in trace amounts in the water. Analysis of the metal concentrations in water, sediment and fish muscle tissue revealed that the sediment contained the highest concentrations of metals followed by fish tissue and then the water. Metals that were detected in the water column includes; aluminium, antimony, arsenic, barium, boron, iron, manganese, selenium, strontium and tin. Metals that were detected at concentrations above the TWQR for aquatic ecosystem were; aluminium, antimony and selenium. Arsenic, cadmium and chromium were recorded at concentrations above the detection limit as suggested by CCME. Zinc concentrations were recorded at levels below suggested detection limit. Aluminium, barium, boron, cadmium, chromium, manganese, selenium and strontium were all detected at elevated levels in water and above the TWQR. Among the metals recorded in the water column, significant seasonal variations in concentration were found for aluminium, barium, boron, lead selenium and strontium whereas only boron showed a significant variation between sites. In comparison to the metals concentrations accumulated in the muscle tissue of both fish species. It was noted that C.gariepinus accumulated more metals than L. rosae; however L. rosae accumulated more metals at elevated concentrations than C. gariepinus. The metals that were accumulated at elevated levels in C. gariepinus were barium, boron, zinc and selenium. In L. rosae, iron, aluminium, strontium, titanium, vanadium and arsenic accumulated at elevated levels. All these metals pose a high risk to fish and human’s health. The highest population HAI was recorded in summer for both fish species. The lowest HAI value was recorded in autumn for both fish species. Although a high HAI population value was recorded higher in summer for both fish species, in general both fish species from the barrage were in a normal condition. A high number of ectoparasites were recorded in L. rosae than in C. gariepinus while high numbers of endoparasites were recorded in C. gariepinus than L. rosae. The dominating ectoparasites for both species were from the class monogenea. Although the prevalence for Contracaecum sp. in C. gariepinus was 100% in all season, it did not influence the condition of the host. None of the parasites identified from both fish species neither reached alarmingly infection levels nor caused any visible damage to the host. In conclusion, the water quality at the Phalaborwa Barrage is slightly polluted based on the water quality parameter(phosphorous) presence and recorded of some metals at the inflow that were recorded at elevated levels above the TWQR. Further recommendations are refereed such as extension of this study to all tributaries and to include other fish species in addition to constant monitoring of the impoundment.
Thesis (M.Sc. (Zoology)) --University of Limpopo, 2014
Keywords: Water Pollution; Water Purification; River Sediments; Olifants River; Phalaborwa; 363.73940968; River sediments - Quality; Water - Pollution - Law and legislation; Freshwater biodiversity; Water purification